2021
DOI: 10.1002/ange.202013540
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Asymmetric Hydrogenation of Quinolines Enabled by π–π Interaction**

Abstract: The non-noble metal-catalyzed asymmetric hydrogenation of N-heteroaromatics, quinolines, is reported. A new chiral pincer manganese catalyst showed outstanding catalytic activity in the asymmetric hydrogenation of quinolines, affording high yields and enantioselectivities (up to 97 % ee). A turnover number of 3840 was reached at a low catalyst loading (S/C = 4000), which is competitive with the activity of most effective noble metal catalysts for this reaction. The precise regulation of the enantioselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Lui et al (2020) developed the first non-noble metal catalyzed reaction of N-heteroaromatics (Scheme 32). 87,88 They reported that the catalytic system applied to reaction of 2-substituted quinoline and bis (quinoline-2-yl) methene, and 1,4 dioxan was used as solvent. This synthesis gave excellent yield and enantioselectivity.…”
Section: Mn Catalyzed Synthesismentioning
confidence: 99%
“…Lui et al (2020) developed the first non-noble metal catalyzed reaction of N-heteroaromatics (Scheme 32). 87,88 They reported that the catalytic system applied to reaction of 2-substituted quinoline and bis (quinoline-2-yl) methene, and 1,4 dioxan was used as solvent. This synthesis gave excellent yield and enantioselectivity.…”
Section: Mn Catalyzed Synthesismentioning
confidence: 99%
“…[5] There has also been a collection of interesting papers reporting Mn catalysts for enantioselective hydrogenation, with just a few catalysts pictured in Figure 1 for brevity. [3][4][5] In terms of enantioselective ketone hydrogenation, there were various limitations in substrate scope. We felt this catalyst family merited our focus due to offering good reactivity for a range of substrates, and that further mechanistic knowledge would be the best way to unleash enhanced substrate scope in highly enantioselective hydrogenations.…”
mentioning
confidence: 99%
“…[1] This includes both identifying new opportunities and solving known problematic reactions. This has overlapped with the early stages of a current major topic of research effort focused on developing the reactivity of earth abundant metal hydrogenation catalysts; [2][3][4] manganese catalysts [3][4][5] are very promising and of high current interest. The advantages of Mn catalysts are well-known; an indefinitely sustainable supply of Mn salts are available for the catalysis industry, whilst also presenting lower toxicity concerns than precious metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation